"Keep your town sweet and wholesome" : the inspector of nuisances : a narrative of culture and sanitation in nineteenth-century Durban (Historia, 2021)
The nineteenth-century colonial town of Durban became a place where a growing British sanitation culture met headlong with the different attitudes of other urbanising people. The inspector of nuisances and the municipality's Sanitary Committee played a significant role in this context and tried to deal with a great variety of environmental problems. Some, such as overcrowded slums, led specifically to far-reaching consequences such as formal segregation policies. The inspectors were also concerned with many other types of nuisances including the need for hygiene; loafers and togt workers, barracks and compounds and the inspection of buildings. They played an important role in the development and refinement of urban services such as the night-soil system and the manufacture of fertilising manure.  In die negentiende-eeuse koloniale dorp, Durban, het die ontwikkelende Britse sanitasiekultuur lynreg gebots met die diverse sieninge van ander groepe in die proses van verstedeliking. Die "Inspekteur van Verontreiniging" en die Munisipale Sanitêre Komitee het 'n betekenisvolle rol in hierdie konteks gespeel en moes 'n verskeidenheid van omgewings-probleme hanteer. Sommige, soos oor-besette krotbuurte, het vêrreikende gevolge gehad: 'n Formele segregasie beleid. Die Inspekteurs was ook gemoeid met verskeie ander stoornisse: die behoefte aan higiëne; leeglêers en togarbeiders; barakke en kampongs en geboue-inspeksie. Hulle het 'n belangrike rol vervul in die ontwikkeling en verfyning van stedelike dienste soos die nagvuil stelsel en die vervaardiging van misstof vir bemesting.
Keywords: Lokasies; Armoede; Public nuisances; Siektes; Oor-besetting; Durban; Afval-verwydering; Versameling en behandeling van nagvuil (sanitere afval); Sanitere Komitee; Disease; Collection and treatment of nightsoil; Poverty; Segregation; Bou-inspekteurs; Sanitary Committee; Inspector of nuisances; Openbare stoornisse; Inspekteur van Verontreiniging; Building inspections; Locations; Rubbish collection; Overcrowding